Pengaruh Book Tax Differences dan Volatilitas Arus Kas terhadap Persistensi Laba - Erika Inas Camille; Effriyanti Effriyanti (EkoPreneur, 2020)
This study aims to analyze the effect of the Book Tax Differences and cash flow volatility on earnings persistence. This research was conducted on goods and consumption subsector manufacturing companies listed on the Indonesia Stock Exchange (BEI) for the 2016-2019 period. This research uses a descriptive quantitative method and determines the number of samples used by purposive sampling and obtained 11 companies with a period of 4 (four) years, so the total data obtained is as much as the sample data. To test the hypothesis using the SPSS version 25 program and the data were analyzed using the multiple linear regression analysis methods. The results of the T analysis show that partially the difference in book-tax does not affect earnings persistence, the difference in book-tax has a positive effect on earnings persistence and cash flow volatility has a positive effect on earnings persistence. And the F test results can be seen that the difference and book-tax volatility simultaneously has a positive effect on earnings persistence.Keywords: Book Tax Differences, Cash Flow Volatility, Earnings Persistence